The lighthouse war - McKinty, Adrian (New York : Amulet Books, 2007)
When Jamie and Ramsay answer a summons to return to Altair, accompanied by Ramsay's cousin Brian, they learn that the Witch Queen wants to capture the Salmon from them and use it to transport her people from that dying planet to Earth--and that Jamie's beloved Wishaway has agreed to marry someone else.
Keywords: Space and time -- Juvenile fiction; War stories; Magic -- Juvenile fiction; Space and time -- Fiction; War -- Fiction; Magic -- Fiction; Science fiction; Young adult fiction; Ireland -- Juvenile fiction; Ireland -- Fiction